Representasi Religiositas (Parahyangan) Dalam Cerpen Pintu dan Pekak Gede Karya IBW Widiasa Keniten - Ida Ayu Trisna Adiwulandari; I Nyoman Darma Putra; Ni Ketut Ratna Erawati (Jurnal Penelitian Agama Hindu, 2026)
Previous studies on tri hita karana in modern Balinese literature have largely emphasized normative and descriptive perspectives, while analyses that approach literary texts as spaces for the production and negotiation of religiosity remain limited. This study aims to examine the representation of parahyangan religiosity in the short stories Pintu and Pekak Gede by IBW Widiasa Keniten. Employing a qualitative descriptive design, this research conducts close textual analysis of narrative passages, dialogues, symbols, characters, and settings that articulate the relationship between humans and God. Data were collected through intensive reading, then selected and thematically classified before being interpreted in relation to cultural meaning-making processes. The findings indicate that parahyangan religiosity in both short stories is represented a reflective cultural practice that is continuously reconfigured rather than a static normative doctrine. Religious symbols function as media for the production of meaning that articulate and legitimize the characters’ spiritual experiences. The characters are constructed as religious subjects who continuously negotiate tradition, personal experience, and social change, thereby revealing the shifting transformative of religious subjectivity in contemporary Balinese society. Furthermore, the settings operate as discursive spaces that integrate sacred and social dimensions, showing how religiosity is embedded in ordinary social practices.This study demonstrates that modern Balinese short stories do not merely symbolically represent religious values but also produce new meanings of parahyangan within the context of contemporary Balinese culture. These findings confirm that literature serves as a reflective and critical space for reinterpreting local religiosity amid ongoing social and cultural change.